2011
DOI: 10.1021/jp2022743
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Reaction Rate Constants Computed Using Semiclassical Transition-State Theory: HO + H2 → H2O + H and Isotopologues

Abstract: A new algorithm [Nguyen, T. L.; Stanton, J. F.; Barker, J. R. Chem. Phys. Lett. 2010, 9, 499] for the semiclassical transition-state theory (SCTST) formulated by W. H. Miller and co-workers is used to compute rate constants for the isotopologues of the title reaction, with no empirical adjustments. The SCTST and relevant results from second-order vibrational perturbation theory (VPT2) are summarized. VPT2 is used at the CCSD(T) level of electronic structure theory to compute the anharmonicities of the fully co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
150
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(154 citation statements)
references
References 56 publications
(106 reference statements)
4
150
0
Order By: Relevance
“…which has almost the same activation barrier and effective mass as reaction (12) (Nguyen et al 2011, Table 2). In the OH/H 2 co-deposition experiment described in the previous section, the reaction products were basically the same as those of the H 2 O-fragment deposition except for the presence of O 3 .…”
Section: Od + Hmentioning
confidence: 75%
See 4 more Smart Citations
“…which has almost the same activation barrier and effective mass as reaction (12) (Nguyen et al 2011, Table 2). In the OH/H 2 co-deposition experiment described in the previous section, the reaction products were basically the same as those of the H 2 O-fragment deposition except for the presence of O 3 .…”
Section: Od + Hmentioning
confidence: 75%
“…For convenience, hereafter, these three groups are denoted A, B, and C, respectively. Although the difference in the barrier height (ΔE a ) among the reactions listed in Table 2 is small (ΔE a < ∼400 K; Talukdar et al 1996;Nguyen et al 2011), it is remarkable that a considerable isotope effect was clearly observed in groups A and B. The reactions differed intrinsically depending on whether the reaction involved H-or D-atom abstraction, and the effective masses were comparable within a reaction group, as shown in Table 2.…”
Section: Relative Reaction Efficiencymentioning
confidence: 94%
See 3 more Smart Citations